THE INFLUENCE OF THE WORK ENVIRONMENT, COMPETENCE AND SERVICE SYSTEM ON JOB SATISFACTION THROUGH WORK MOTIVATION AT THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION OF KARIMUN REGENCY - HUTASOIT, HASUDUNGAN (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
The purpose of this study was to determine the effect of the work environment, competence and service system on job satisfaction through work motivation. This type of research is descriptive research. Hypothesis testing is done by using multiple regression test. The sampling technique used is a saturated sample. The sample of this study were all employees within the Department of Population and Civil Registration of Karimun Regency, amounting to 70 people. Data processing using SmartPLS 3.0 software. The research method used as a descriptive statistical data analysis tool and Partial Least Square (PLS-SEM) is a method of analyzing data to predict and develop an existing theory. The results showed that partially the work environment had a positive and significant influence on job satisfaction,